Hypolaetin-7-O-β-D-xyloside from Juniperus communis Fruits Inhibits Melanogenesis on Zebrafish Pigmentation - Jeong, Eun Ju; Jegal, Jonghwan; Chung, Ki Wung; Noh, Sang Gyun; Chung, Hae Young; Nam, Youn Hee; Kang, Tong Ho; Kim, Su-Nam; Yang, Min Hye (SAGE PUBLICATIONS INC, 2017)
Hypolaetin-7-O-beta-D-xyloside (1) is a naturally occurring flavonoid from Juniperus communis fruits. This study aimed to investigate anti-melanogenic effect of hypolaetin-7-O-beta-D-xyloside on zebrafish pigmentation. The phenotype-based image analysis suggested that 1 suppressed the zebrafish pigmentation in a concentration-dependent manner (1-400 mu M) as a reversible competitive inhibitor against the enzyme tyrosinase. According to the molecular docking simulation, the compound 1 interacted with residues His-263 of tyrosinase via hydrogen bonding. The present study provided direct experimental evidence for skin-lightening effect of 1 in an in vivo zebrafish model. Therapeutic attempts with the 1 might be useful in the management of skin pigmentation-related diseases.